Frozen Food Should Be An Alternative At The Pandemic Covid-19 - et. al., Galuh Boga Kuswara, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to find out how much influence the atmosphere of A-H Jaya Frozen Food Store and the price of A-H Jaya Frozen Food Store products in influencing consumer purchasing decisions at A-H Jaya Frozen Food Subang Store during the Covid-19 Pandemic. This research uses descriptive and verification methods, in addition to that in this study using the counting method with Path Analysis and processed using the LISREL for Students program. The population in this study was unknown and took samples using an iterative technique which resulted in a sample of 115 respondents. In addition, data collection in this study was carried out by distributing questionnaires and interviewing respondents directly. This research is equipped with managerial implications that can be useful for the company / organization studied in this study to solve internal and external problems in the A-H Jaya Frozen Food Store environment. The results of this study indicate that the questionnaire distributed shows valid and reliable results and all processed variables show a significant effect. The value of t is greater than the value of t table, namely the value of the store atmosphere variable is 10.86> 1.65 and 6.29> 1.65, while simultaneously fcount is also greater than the table value, namely 7.51> 3.08. The effect of the store atmosphere shows a greater influence than the product price, which is 37.9%, while the product price variable has an effect of 12.9%. The effect of the two variables shows the effect of 53.4% and is a strong influence to influence consumer purchasing decisions.